SCARB2 mutations as modifiers in Gaucher disease: the wrong enzyme at the wrong place? - Coutinho, Maria Francisca (2019)
Unlike most lysosomal proteins, β-glucocerebrosidase (GCase), the hydrolase defective in Gaucher disease (GD), is delivered to lysosomes through its interaction with the transmembrane protein LIMP2. A few years ago, mutations in its coding gene, SCARB2, were reported to modify the severity of GD phenotype. The existence of a great variety of GD phenotypes is well-known, with numerous patients who carry identical genotypes presenting remarkable phenotypic variability. Over the years, that variability has been attributed to other genetic, epigenetic and/or environmental factors. Still, there is still much to learn on this subject. Recently, an association between Parkinson's disease (PD) and the presence of mutations in the GBA gene has been demonstrated. Moreover, there are also studies suggesting that genetic variants in the SCARB2 gene may also be risk factors for PD. We analysed the SCARB2 gene in the Portuguese cohort of 91 GD patients, having identified 3 different SCARB2 coding variants. Of those, 2 were known polymorphisms with high prevalence in the normal population (p.M159V and p.V396I) and the third was a novel coding variant, p.T398M, present in heterozigousity in a single patient. Our study demonstrated that, at least for the Portuguese population, genetic variability at SCARB2 does not account much to the GD phenotypic spectrum. Nevertheless, in vitro analyses of the novel p.T398M are envisaged, in order to further characterize the effect of this variant on the levels and sub-cellular location of GCase. The clinical presentation of the patient harbouring this coding variant will also be discussed.